Continuity and discontinuity in the human use of the north coast of Santa Cruz (Patagonia Argentina) through its radiocarbon record - Zubimendi, Miguel Angel (2015)
In this paper, the analysis of a radiocarbon database of the North Coast of Santa Cruz (central Patagonia, Argentina), is presented. Dated archaeological samples were obtained from 56 different types of archaeological sites (open-air -residential sites and burials-, and also rock shelters). The objective of this paper is assessing the continuities and discontinuities in the chronological signal of the area and identifying tendencies along the Holocene. The database currently contains 75 radiocarbon dates falling between ca. 8000 and 300BP. The radiocarbon data base provides information on the chronological, spatial and contextual variability of the archaeological record of North Coast of Santa Cruz. By means of different analysis of sum of probabilities, we present three different chronological moments of human use of the coast and intermediate zone can be identified. A first moment is represented by early evidence of settlement during Middle Holocene. A second moment corresponds to a hiatus between ca. 5800 and ca. 3900BP without archaeological evidence. Finally, a third moment is where an increasing of chronological signal occurred, related to greater artifactual variability and an increase in the intensity of human settlement in the Patagonian region. The causes that could have influenced in the discontinuity of the chronological signal of the study area, and the characteristics of the different moments identified are discussed.